Bahasa Inggris External Motivation (Work Environment) and Burnout Incidence in ER and ICU Nurses - Murharyati, Atiek; Diani, Nova Okta; Sulisetyowati, Dwi; Safitri, Wahyuningsih (Adi Husada Nursing Journal, 2023)
Burnout is exhaustion syndrome both mentally and Burnout is a syndrome of exhaustion both mentally and physically which can lead to boredom. The work environment is something that exists around workers that can affect the results of their performance. The research method adopted quantitative with a cross-sectional approach of 30 people sample. The sampling used a non-probability sampling technique, and the study was conducted at RSUD Surakarta. The results of this study presented a significant relationship between external motivation (work environment) and burnout in nurses in the emergency room and ICU at the Surakarta City Regional General Hospital with an average score of mild burnout of 26 (86.7%), a moderate burnout level of 4 (13.3) and a burnout level of 0 (0%). Meanwhile, the results of the value of external motivation (work environment) indicated a poor work environment with 30 (100%). Even though the work environment is not good, it has a burnout level due to good stress coping in the emergency room and ICU at the Surakarta City General Hospital. The program of joint activities such as gymnastics, picnics, and helping each other can reduce the incidence of burnout in the emergency room and ICU at the Regional Public Hospital of Surakarta City